2011
DOI: 10.1016/j.radonc.2011.05.057
|View full text |Cite
|
Sign up to set email alerts
|

TRIB3 protein denotes a good prognosis in breast cancer patients and is associated with hypoxia sensitivity

Abstract: Whereas mRNA levels of TRIB3 are related with a poor prognosis, TRIB3 protein is associated with a good prognosis in human breast cancer patients, possibly due to the fact that TRIB3 is involved in hypoxia tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 27 publications
1
54
2
Order By: Relevance
“…Likewise, high TRIB3 protein levels are associated with good prognosis in breast cancer patients. 36 In addition, TRIB3 is focally deleted in tumors of epithelial origin (tumorscape data set; Supplementary Table SI), thus supporting that loss or downregulation of TRIB3 is an event associated with human cancer. Nevertheless, other studies have found an upregulation of TRIB3 mRNA levels in human cancers.…”
Section: Discussionmentioning
confidence: 77%
“…Likewise, high TRIB3 protein levels are associated with good prognosis in breast cancer patients. 36 In addition, TRIB3 is focally deleted in tumors of epithelial origin (tumorscape data set; Supplementary Table SI), thus supporting that loss or downregulation of TRIB3 is an event associated with human cancer. Nevertheless, other studies have found an upregulation of TRIB3 mRNA levels in human cancers.…”
Section: Discussionmentioning
confidence: 77%
“…Some laboratories reported elevated TRIB3 mRNA levels which correlated with bad prognosis in colorectal cancer (46) and breast cancer patients (47). On the other hand, high TRIB3 protein levels have been associated with good prognosis sensitivity to radiotherapy in breast cancer patients (48). As TRIB3 is a very stable protein (49), the discrepancies observed between TRIB3 mRNA and protein levels in human breast cancer prognosis might be due to posttranslational modifications, still to be described, that might modulate the ability of TRIB3 to interact with other proteins that regulate tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to NGF withdrawal, Trib3 is induced by a variety of cellular stresses relevant to neurons, including the unfolded protein response and ER stress, nutrient deprivation, anoxia and ethanol exposure. [20][21][22][23][24][25]27,28,30,36 Given this and Trib3's suppression of Akt signaling, it can be anticipated that Trib3 is a participant in, and therefore a potential target for treatment of, a variety of neurological disorders and insults.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 In addition to NGF deprivation, Trib3 mRNA is upregulated by stresses, including hypoxia, ER stress and 6-hydroxydopamine treatment. [20][21][22][23] The range of functions attributed to Trib3 include regulating glucose homeostasis, promoting tumor cell migration, suppressing adipocyte differentiation, inhibiting ER stress and either promoting or inhibiting cell death. [24][25][26] Trib3 is a pseudokinase with an inactive catalytic domain.…”
mentioning
confidence: 99%